Animal board invited review: Animal source foods in healthy, sustainable, and ethical diets - An argument against drastic limitation of livestock in the food system - Leroy, F.; Abraini, F.; Beal, T.; Dominguez-Salas, Paula; Gregorini, P.; Manzano, P.; Rowntree, J.; Vliet, S. van (Elsevier, 2022)
Animal source foods are evolutionarily appropriate foods for humans. It is therefore remarkable that they are now presented by some as unhealthy, unsustainable, and unethical, particularly in the urban West. The benefits of consuming them are nonetheless substantial, as they offer a wide spectrum of nutrients that are needed for cell and tissue development, function, and survival. They play a role in proper physical and cognitive development of infants, children, and adolescents, and help promote maintenance of physical function with ageing. While high-red meat consumption in the West is associated with several forms of chronic disease, these associations remain uncertain in other cultural contexts or when consumption is part of wholesome diets. Besides health concerns, there is also widespread anxiety about the environmental impacts of animal source foods. Although several production methods are detrimental (intensive cropping for feed, overgrazing, deforestation, water pollution, etc.) and require substantial mitigation, damaging impacts are not intrinsic to animal husbandry. When well-managed, livestock farming contributes to ecosystem management and soil health, while delivering high-quality foodstuffs through the upcycling of resources that are otherwise non-suitable for food production, making use of marginal land and inedible materials (forage, by-products, etc.), integrating livestock and crop farming where possible has the potential to benefit plant food production through enhanced nutrient recycling, while minimising external input needs such as fertilisers and pesticides. Moreover, the impacts on land use, water wastage, and greenhouse gas emissions are highly contextual, and their estimation is often erroneous due to a reductionist use of metrics. Similarly, whether animal husbandry is ethical or not depends on practical specificities, not on the fact that animals are involved. Such discussions also need to factor in that animal husbandry plays an important role in culture, societal well-being, food security, and the provision of livelihoods. We seize this opportunity to argue for less preconceived assumptions about alleged effects of animal source foods on the health of the planet and the humans and animals involved, for less top-down planning based on isolated metrics or (Western) technocratic perspectives, and for more holistic and circumstantial approaches to the food system.